Maximum Likelihood Methods for Models of Markets in Disequilibrium - Maddala, G. S.; Nelson, Forrest D. (Econometrica, 1974)
[The paper presents maximum likelihood methods for estimating four types of disequilibrium models. In each case the model includes three equations: the demand equation, the supply equation, and the condition that quantity observed is the minimum of quantity demanded and quantity supplied. The first model consists of just these equations. In the second model one knows whether one is on the demand function or the supply function by looking at the direction of the change in price. In the third model the price change is assumed to be proportional to excess demand. In the fourth model the price change is a stochastic function of excess demand and possibly other exogenous variables. Some illustrative calculations are presented using the housing starts model considered by Fair and Jaffee in an earlier issue of this journal.]